User recognition mechanism and user contribution behavior in enterprise-hosted online product innovation communities: Based on prosocial behavior theory. Issue 1 (21st February 2019) - Qin, Min; Liang, Su
Abstract : Purpose: This paper aims to conceptualize two patterns of user recognition mechanisms and two kinds of user contribution behavior in enterprise-hosted online product innovation community and explain their relationships between user recognition mechanisms and user contribution behavior of online product innovation community. Design/methodology/approach: A Chinese enterprise-hosted online innovation community and an American enterprise-hosted online innovation community are selected as research objects. Four Logit models are developed and some hypotheses are supposed from the perspective of prosocial behavior theory. Objective user data with three months from two online product innovation communities are collected to test with Logit regression analysis. Findings: Findings show that there are obvious correlations between user recognition mechanisms and user contribution behavior, and there is also an obvious difference in community user activity level between the quantity-based user recognition mechanism community and the quality-based user recognition mechanism community. More specifically, in the online product innovation community with quantity-based recognition mechanism, both variables of peer recognition and community image motivation significantly affect user proactive contribution behavior. In the online product innovation community with quality-based recognition mechanism, the variable of peer recognition significantly affects both user proactive contribution behavior and user responsive contribution behavior; the variable of community image motivation significantly affects both user proactive contribution behavior and user responsive contribution behavior. Practical implications: Although it is voluntary, online user voluntary contribution behavior still need to be presented, recognized and affirmed by community. For enterprise-hosted online community managers, they should pay more attention to design the reasonable online community user recognition mechanism with the coexistence of quantity and quality. Originality/value: The theoretical contribution in this study is to enrich the existing research theme about enterprise-hosted online product innovation community. First, it conceptualizes two patterns of user recognition mechanisms. Second, it regards the variable of user contribution behavior as the co-existence of proactive contribution and responsive contribution. Third, from the perspective of prosocial behavior theory, it is an important supplement to explain the mechanism of user contribution behavior in enterprise-hosted online product innovation community. Fourth, it deepens the overall understanding of the relationship between user recognition mechanism and user contribution behavior. This study provides theoretical guidance for enterprises how to design reasonable and efficient online product innovation community platform. The theoretical contribution in this study is to enrich the existing research theme about enterprise-hosted online product innovation community. First, it conceptualizes two patterns of user recognition mechanisms. Second, it regards the variable of user contribution behavior as the co-existence of proactive contribution and responsive contribution. Third, from the perspective of prosocial behavior theory, it is an important supplement to explain the mechanism of user contribution behavior in enterprise-hosted online product innovation community. Fourth, it deepens the overall understanding of the relationship between user recognition mechanism and user contribution behavior. This study provides theoretical guidance for enterprises how to design reasonable and efficient online product innovation community platform.